The Role of Experts in the Covid-19 Pandemic and the Limits of Their Epistemic Authority in Democracy - Lavazza, Andrea; Farina, Mirko (Frontiers in Public Health, 2020)
In the 2020 Covid-19 pandemic, medical experts (virologists, epidemiologists, public health scholars, and statisticians alike) have become instrumental in suggesting policies to counteract the spread of coronavirus. Given the dangerousness and the extent of the contagion, almost no one has questioned the suggestions that these experts have advised policymakers to implement. Quite often the latter explicitly sought experts' advice and justified unpopular measures (e.g., restricting people's freedom of movement) by referring to the epistemic authority attributed to experts. The main goal of this paper is to analyze the basis of this epistemic authority and the reasons why in this case it has not been challenged, contrary to the widespread tendency to devalue expertise that has been observed in recent years. In addition, in relation to the fact that experts' recommendations are generally technical and supposedly neutral, we note that in the COVID-19 crisis different experts have suggested different public health policies. We consider the British case of herd immunity and the US case of the exclusion of disabled people from medical care. These decisions have strong axiological implications and affect people profoundly in very sensitive domains. Another goal is, therefore, to argue that in such cases experts should justify their recommendations-which effectively become obligations-by the canons of public reason within the political process because when values are involved it is no longer just a matter of finding the “best technical solution,” but also of making discretionary choices that affect citizens and that cannot be imposed solely on the basis of epistemic authority.